Genetic and physiological characteristics of CsNPR3 edited citrus and their impact on HLB tolerance - Tiwari, Trishna; Robertson, Cecile; El-Mohtar, Choaa; Grosser, Jude; Vashisth, Tripti; Mou, Zhonglin; Dutt, Manjul (Frontiers in Genome Editing, 2024)
Huanglongbing (HLB) disease, caused by Candidatus Liberibacter asiaticus (CaLas), severely impacts citrus production, and currently, there is no cure. Developing HLB-resistant or tolerant cultivars is crucial, with modifying defense-related genes being a promising approach to managing HLB. NONEXPRESSOR OF PATHOGENESIS-RELATED GENES 1 (NPR1) is a positive regulator of systemic acquired resistance (SAR), which enhances resistance to pathogens, whereas NONEXPRESSOR OF PATHOGENESIS-RELATED GENES 3 (NPR3) is a negative regulator of SAR. To unambiguously address the role of CsNPR3 in HLB, we introduced mutations into the CsNPR3 gene in sweet orange (Citrus sinensis L. Osbeck) through genome editing and assessed their effects on morphology, physiology, and resistance/tolerance to HLB. Several genome-edited 'Hamlin' sweet orange trees harboring frameshift-inducing insertions or deletions were identified. After confirming the genome editing using Sanger sequencing, selected lines were grafted onto C-146 trifoliate hybrid rootstocks for clonal propagation. The progenies were then infected with CaLas using a no-choice Asian Citrus Psyllid (ACP) feeding assay. Evaluation of the genetic and physiological characteristics of CsNPR3-edited citrus trees under greenhouse conditions revealed that the edited trees exhibited greater vigor than the wild-type trees, despite the lack of significant differences in CaLas titers. Although further field evaluation is needed, our findings indicate that CsNPR3 contributes to HLB-caused tree deterioration and demonstrate that editing CsNPR3 can enhance tolerance to HLB.